A Series of Manganese(III) Salen Complexes as a Result of Team‐Based Inquiry in a Transnational Education Programme. Issue 6 (9th June 2020) - Yuan, Danlei; Cai, Ningqi; Xu, Jingxi; Miao, Danyang; Zhang, Sheng; Woodfine, Sian E.; Plana, Daniela; Hawes, Chris S.; Watkinson, Michael
Abstract: The development of a team‐based approach to research‐led transnational practical chemistry teaching is described in which a team of five Chinese students on an articulated transnational degree programme, supported by a team of academic and technical staff, carried out a study examining the structural chemistry of a series of manganese(III) salen complexes. A series of four crystallographically characterized manganese(III) salen complexes with ancillary carboxylate ligands are reported here. The carboxylate coordination modes range from the bridging syn ‐ anti μ 2 ‐κO : κO′ mode observed in the predominant cyclohexanoate and isobutyrate species, to a capping terminal monodentate mode for the adamantanoate species, and an unusual mixture of bridging and terminal coordination modes observed in a second minor phase of the cyclohexanoate species. The variation on extended structures based on the weakly interacting aliphatic backbones may provide a useful basis for further structural studies. Abstract : Bridging the divide : A team‐based inquiry approach to transnational chemistry education and attempts to scaffold laboratory work into a standalone group research project focusing on the structural chemistry of manganese(III) Schiff base complexes is reported. The findings of that project are also presented where four new manganese(III) salen complexes with carboxylate bridges have been prepared and characterized.